A new species of the spider genus Mallinella Strand, 1906 from Yintiaoling Nature Reserve, China (Araneae: Zodariidae) - Lu, Jin-Zhen; Irfan, Muhammad; Zhang, Zhi-Sheng (Zootaxa, 2025)
A new species belonging to the Mallinella annulipes-group of the genus Mallinella Strand, 1906, Mallinella yintiaoling sp. nov. (male, female), is described from Yintiaoling Nature Reserve, China. Its morphological description and photographs are provided.